2016
DOI: 10.1097/bpo.0000000000000412
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Orthopaedic Malpractice Claims of Pediatric and Adult Patients in Private Practice

Abstract: There appear to be moderate differences in outcomes of orthopaedic malpractice claims between adult and pediatric patients. The longer statute of limitations associated with pediatric claims does not appear to portend a less favorable medicolegal outcome or excessively longer time to claims filing for pediatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 13 publications
4
12
0
Order By: Relevance
“…Our study showed that pediatric orthopedics is associated with a high incidence of compensation claims, which confirms findings by other authors, both from the United States (Oetgen andParikh 2016, Galey et al 2019).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our study showed that pediatric orthopedics is associated with a high incidence of compensation claims, which confirms findings by other authors, both from the United States (Oetgen andParikh 2016, Galey et al 2019).…”
Section: Discussionsupporting
confidence: 92%
“…The granting percentage in our material was 31%, comparable to findings by Oetgen and Parikh (2016), who found 33%. Galey et al (2019) in a US study found a granting percentage of 51%.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…genic cast saw abrasions and thermal burns occur with a frequency of 0.72% and are common sources of litigation, accounting for up to 4.7% of filed claims and having reported settlements greater than $12,000 per patient. [9][10][11] Further, a split cast may result in loss of fracture reduction, requiring either additional manipulation of the cast, repeat reduction under sedation, or surgical stabilization. 12 The objectives of this single-center, prospective randomized controlled study of pediatric forearm fractures requiring acute reduction and casting were to examine the impact of cast valving on the rates of (1) cast-related complications such as compartment syndrome or cast saw injury and (2) fracture remanipulation or the need for subsequent operative intervention.…”
mentioning
confidence: 99%